“As you walked next to death ...”: The Dantesque Iter of Kazantzakis’s Zorba the Greek - Watt, Mary (Spunti e Ricerche, 2022)
This article will examine first, how Kazantzakis, like Dante, absorbs the landscape of his own journey of exile to create the landscape of his iconic story of the quest for salvation. It will then consider how Kazantzakis uses the figure of Dante, the pilgrim-poet, to lend an inter-textual layer to the novel that serves as both hermeneutic device and a means of aligning Kazantzakis’s quest with Dante’s. Finally, it will consider how Kazantzakis uses the figure of Ulysses, both Homer’s and Dante’s, presenting him as an “anti-pilgrim,” to expose the futility of the search for heavenly paradise.